ANALISIS RESEP TIDAK TERLAYANI PASIEN RAWAT JALAN DI INSTALASI FARMASI RSU X JAKARTA - Agustina, Ika; Tuahuns, Farida; Charles, Charles; Adina, Arfie Nur (Jurnal Riset Kefarmasian Indonesia, 2023)
Pharmacy service is inseparable from health service system of a hospital. The service of pharmacy unit shall be a priority because an effective and efficient service will affect in the fulfillment of prescriptions. Furthermore, the management on the pharmaceutical stock will influence the revenue of the hospital (part of revenue center). The purpose of this research is to find out the percentage of unfilled prescriptions of outpatients from many different units, its reasons, and Therapeutic Class of unserved drug items. The research applies descriptive method using prospective data i.e. 25,259 R/ sheets of prescriptions obtained by total sampling technique. The research was conducted in three months from February to April 2021. The result of the research shows that there are unfilled 467 R/ prescriptions due to several factors, such as the drugs are not listed in the formularies, the drugs are out of stock, and the prescribed or patient-requested drugs are not covered by the insurance. Internal medicine unit has the most unfilled prescriptions (160 out of 467). The main reason is the drugs are out of stock (133 out of 467). Medicines for Gastritic, Respiratory, Heart Diseases and Allergicare the top lists in the Therapeutic Class, which is in accordance with data showing that Intenal Medicine, Emergency Department dan General Practisioners, Pulmonary, Dermatology and Venereology, and Obstetrics and Gynecology are the top 5 polyclinics with the number of unserved prescriptions due to out of stock.